Legitimidade e hegemonia : o mercado do ensino superior na região de Passo Fundo -- 1990-2005 - Tuzzin, Leandro (2009)
It talks about the changes that happened in the superior education field, in the period between 1990 and 2005. The Law of Directrix and Basis of National Education (LDB), of 1996, built from the neoliberal principles of the Law`s defense of the market, which legalized the participation of private companies in offering superior education. This regulation wanted to wide the access to colleges. The inspiration and reason of such a rule comes from the human capital theory, which got stronger in the world view by keeping the relation between education investment and economic success. With the 1980-1990 crash, the education was rapidly turned into and alternative to the social problems of unemployment and misery. It increased the search for specialization s courses. The private companies, watching this demand existence, started to invest in the area, promoting an expressive growth of the institutions numbers, courses and jobs opportunities to the superior teaching. It was a positive answer to the LDB`s intentions. However, the educational market unwarmed, because of the big increase of idle vacancies, meanly in the private institutions. The fact had the institutions to adopt many strategies to keep themselves working, but also showed some limits. The business lived a moment of great competitiveness. At Deep Step region, the transformation of the educational shape got striking features. There were some shots to avoid the market open, from the Deep Step University, which tried to keep the community university model practiced for itself since then. Anyway, the LDB purpose of increasing the superior education market was reached in the region, where others Superior Teach Institutions were born and installed